Analysis of Business Uncertainty in The Reefer Container Sector in The Vuca Era of Industry 4.0 (Case Study of Shipping Company Domestic Route) - Winoto Hadi; Nur Azisah; Egy Andarwati S T F (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
This study examines the phenomenon of uncertainty in the reefer container business within the VUCA era (Volatility, Uncertainty, Complexity, Ambiguity), focusing on a domestic route case study of Shipping Company. The background of this research lies in the demand for fresh product delivery, which faces uncertainties in market conditions. The objective of the study is to identify the factors of uncertainty, classify their impacts based on relevant divisions, and provide mitigation solutions. The research methodology employed is a qualitative case study, involving observations, questionnaires, and documentation. The findings reveal that uncertainties stem from government policies, delays in vessel schedules, and fluctuations in operational costs such as fuel prices and freight tariffs. The study concludes that cross-division collaboration and improved mitigation strategies are crucial to maintaining business stability. It is recommended that Shipping Company enhance employee training, strengthen technology integration, and establish strategic partnerships with logistics partners to minimize the impact of uncertainties.